Acute Pancreatitis as an Unusual Culprit of Diabetic Ketoacidosis in a Nondiabetic: A Case-Based Review - Steven Imburgio; Apurva Vedire; Harshavardhan Sanekommu; Anmol Johal; Sobaan Taj; Christopher Lesniak; Arman Mushtaq (Case Reports in Endocrinology)
Acute pancreatitis has been associated with a multitude of complications including pancreatic necrosis, pseudocysts, abscesses, acute respiratory distress syndrome, disseminated intravascular coagulation, and hyperglycemia. To date, only rare case reports have demonstrated diabetic ketoacidosis (DKA) as a rare sequela of acute pancreatitis. We report a case of a 34-year-old female with no prior history of diabetes who was subsequently diagnosed with DKA after presenting with severe acute pancreatitis. This case serves as a framework to not only highlight DKA as a rare complication of acute pancreatitis but also to explore the potential pathophysiology that underlies this phenomenon including stress hyperglycemia and post-pancreatitis diabetes mellitus.